"Coal [from Colombia] is our life". Bourdieu, the miners (after they are miners) and resistance in As Pontes. (June 2021) - Pérez-Sindín, Xaquín S.; Van Assche, Kristof
Abstract: We address the question why social identities associated with resource extraction can survive the extraction itself, a question which is highly relevant for devising strategies for economic diversification and community reinvention in many communities. The case of As Pontes, in Galicia, Spain, where a rural community transformed into a powerhouse of coal mining and electricity production, is highly instructive, as it reveals the importance of state planning and a central actor which structured social, political and economic life, and created identities which could not easily be dislodged. We deploy notions from Pierre Bourdieu's sociology of practice to analyze the persistence of identities and associated hopes for an impossible return to the past, giving central place to the idea of symbolic violence, i.e. the internalization of categories, identities and relations initially promoted by a coalition of actors benefiting from this order of the social field. Highlights: State owned companies dominated the development of space, economy and identity. Identities survive themselves through evolving forms of symbolic violence. Centrally planned forms of development create identities not easy to be dislodged. Regions need thorough reflection on diversification and community reinvention.